Associations between adolescent students’ multiple domain task value-cost profiles and STEM aspirations - Vinni-Laakso, Janica; Upadyaya, Katja; Salmela-Aro, Katariina (Frontiers in Psychology, 2022)
According to the modern expectancy-value theory, students’ task values may differ across domains, manifesting as varying motivational patterns. In middle school, students’ motivation becomes increasingly apparent and may direct their future occupational aspirations. Using a person-oriented approach, this study examines students’ self-concept, and positive and negative task values (i.e., utility value, intrinsic value, and emotional cost) across Finnish language, math, biology, and physics, and the stability of the identified profiles. Further, the associations of the profiles with students’ subsequent academic achievement and math and natural science STEM/health science STEM aspirations, and gendered effects were examined. Longitudinal data was collected through Grades 7 to 9 in 21 middle schools in Helsinki, Finland (N=1309, N=1179, N=818, respectively; age 13-15 years; 55.9% female). Latent profile analysis identified four task value profiles in Grades 7 and 8: Low motivation high cost STEM (13%/13%) showed low task values with high cost, especially in math and physics; High motivation low cost STEM (7%/8%) showed the highest task values with the lowest cost, especially in math and physics; High motivation high cost (18%/17%) showed high task values and cost across domains; and Moderate motivation and cost (62%/62%) showed moderate task values and cost across domains. The latent transition analysis identified Moderate motivation and cost as the most stable profile across two years. In comparison to the other profiles, students with a Low motivation high cost STEM profile were less likely to have STEM aspirations in Grade 9.